Dinâmica paisagística e recursos hídricos: uma análise dos aspectos geoambientais do município de Bonito-MS - ANA FLÁVIA GOMES FERNANDES FONTES (2024)
The landscape is shaped through the relationship between society and nature, so its monitoring is crucial, as some of these transformations tend to cause negative impacts. The agriculture sector in the municipality of Bonito/MS has been growing, contradictorily, to tourist use, with possible environmental impacts on water resources. In this sense, the present research proposed to analyze the dynamics of the landscape and the relationship with the conservation of water resources in the municipality of Bonito/MS. The methodology adopts a qualitative-quantitative approach, with an epistemological basis in line with humanistic geography and systemic analysis. The methodological procedures adopted were: literature review; characterization of the municipality’s socioeconomic and biophysical aspects; preparation of thematic mapping at the municipal level and the Formoso river basin; discursive analysis and comparison with environmental legislation; data collection in public bodies; field survey; application of a sample interview; analysis and interpretation of data. The maps were prepared in the Qgis software, generating the themes of the physical characteristics of the municipality, tourist attractions, land use and coverage, land use and coverage of APPs and spatialization of the field survey points, which aimed to analyze the landscape through records photographs and contacts with representatives of municipal management and tourist attractions to carry out interviews. Afterwards, the data were interpreted, analyzed and discussed. The results point to significant changes in Bonito's landscape, highlighting the municipality's potential for tourist use, the strong advance in agriculture and the importance of APPs and UCs for the conservation of water resources. The need for interventions is concluded regarding the importance of integrated environmental management for the use and conservation of the municipality's landscape, especially regarding water resources.